Ecosystem-Based Fishery Management of Antarctic Krill (Euphausia superba) to Support Baleen Whales and other Predators Production Adapted for Potential Climate Change Effects - R. Hodgson Bruce (Journal of Plant and Animal Ecology, 2025)
Antarctic krill is an important component of the zooplankton production in the Southern Ocean and is a major food source for baleen whales. The role of commercial fishing and predation by whales on Krill abundance has been investigated here using the innovative ecosystem-based fishery management, EBFM which maintains the krill to whale food web ecosystem stability. The literature indicates the Krill fishery may have been overfished, so it was reduced to the current annual upper limit of 0.62 million tonnes for support other predators of krill, such as seals, penguins and flying sea birds. However, recent literature suggests a moderate reduction in krill catch in the Antarctic Peninsula area due to its importance for whale migration to temperate areas. The Peninsula area catch was estimated to be reduced by about 10% due to additional concerns about climate change effects on krill abundance in the Southern Ocean, reducing overall catch to 0.556 million tonnes, moderately higher than the maximum taken in 2022. Hence, the krill biomass fishing was reduced to allow for predation by baleen whales and other predators, giving a full ecosystem-based fishing mortality similar to that previously estimated to maintain krill production in the Southern Ocean.
Keywords: Ecosystem-Based Fishery Management